THE EFFECT OF INSTITUTIONAL OWNERSHIP, INTELLECTUAL CAPITAL, AND COMPANY SIZE TOWARDS COMPANY VALUE - Muhammad Wafiyudin; Bima Cinintya Pratama; Azmi Fitriani; Erny Rachmawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to examine the effect of intellectual capital, institutional ownership, and company size towards firm value. The sample of this study is coal mining listed on the Indonesia Stock Exchange during 2016-2018. Samples were taken using purposive sampling technique, with the acquisition of a total sample of 56 observations. The data analysis technique used is multiple regression analysis using SPSS program. The results of this study indicates that intellectual capital and company size have no effect towards company value, while institutional ownership has a positive effect towards company value.